Predictive contribution of finger-hand grip strength and eye–hand coordination to overhead passing performance: a multiple regression study in novice volleyball players - M. Ihsan Alfajri; Eval Edmizal; Yendrizal Yendrizal; Yogi Arnaldo Putra (Lentera Negeri, 2026)
This study examined the independent and combined contributions of finger-hand grip strength and eye–hand coordination to overhead passing ability among undergraduate students enrolled in a Basic Volleyball Skills course. A quantitative correlational design was employed with 20 male students (from a population of 27) selected through purposive sampling to control for sex-related physical variance. Finger-hand grip strength was measured with a hand-grip dynamometer, eye–hand coordination with a 30-second wall-toss test, and overhead passing ability with a 60-second standardized passing test. Data were analyzed descriptively and inferentially using Shapiro–Wilk normality tests, Pearson product-moment correlation, and multiple correlation/regression in IBM SPSS Statistics (version 26). All variables were normally distributed (p > 0.05). Finger-hand grip strength showed a very strong, significant positive correlation with overhead passing ability (r = 0.891, p < 0.001, R² = 0.794), while eye–hand coordination showed a strong, significant positive correlation (r = 0.638, p = 0.002, R² = 0.407). Jointly, the two predictors explained 90.7% of the variance in passing performance (R = 0.952, R² = 0.907, F(2,17) = 82.90, p < 0.001), with grip strength contributing the larger standardized weight (β = 0.759) relative to coordination (β = 0.362). These findings extend biomechanical models of ball-contact control to a novel population. The research design being correlational in nature, one should see them mainly as a sign that pre-service coaching volleyball teachers could possibly benefit from adding finger-strength and coordination training to their training programs. Of course, this remains true as long as intervention studies confirm it. The study didn't include reliability coefficients for the three measures and also did not carry out the power analysis. These facts point to a limitation of the research.